"Dieselgate:" How Different Approaches to Decentralization, the Role of NGOs, Tort Law and the Regulatory Process Affected Comparative U.S. and European Union Outcomes in the Biggest Scandal in Automotive History. Issue 7 (18th May 2020) - Mujkic, Edin; Klingner, Donald
ABSTRACT: The VW diesel emissions scandal ("dieselgate") recounts how Volkswagen became ensnared in a self-inflicted and staggeringly costly cheating scandal that started in the U.S. and then spread to the European Union. This case study shows how fundamental differences in comparative public administration (CPA) between the U.S. and the European Union (EU) led to different consequences for one of the world's largest and most highly-regarded European auto manufacturers with respect to four institutional variables: (a) approaches to decentralization, (b) the role of non-governmental organizations (NGOs), (c) civil (tort) law, and (d) regulatory environment.